2017
DOI: 10.1097/shk.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

Prevention or Treatment of Ards With Aspirin

Abstract: Background The acute respiratory distress syndrome (ARDS) is a life-threating disorder that contributes significantly to critical illness. No specific pharmacological interventions directed at lung injury itself, have proven effective in improving outcome of patients with ARDS. Platelet activation was identified as a key component in ARDS pathophysiology and may provide an opportunity for preventive and therapeutic strategies. We hypothesize that use of acetyl salicylic acid (ASA) may prevent and/or attenuate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 65 publications
4
34
0
1
Order By: Relevance
“…There has been strong interest in therapeutically targeting platelet activity in ARDS. Although the LIPS-A (Lung Injury Prevention Study with Aspirin) study did not find a reduced risk of ARDS for high-risk subjects randomized to aspirin therapy over placebo, there are ongoing efforts to target platelets for ARDS therapy (11)(12)(13). The gene expression data in the present manuscript strengthens the candidacy of rs9358856 as a functional variant and may contribute to our understanding of platelet homeostasis.…”
supporting
confidence: 58%
“…There has been strong interest in therapeutically targeting platelet activity in ARDS. Although the LIPS-A (Lung Injury Prevention Study with Aspirin) study did not find a reduced risk of ARDS for high-risk subjects randomized to aspirin therapy over placebo, there are ongoing efforts to target platelets for ARDS therapy (11)(12)(13). The gene expression data in the present manuscript strengthens the candidacy of rs9358856 as a functional variant and may contribute to our understanding of platelet homeostasis.…”
supporting
confidence: 58%
“…In line with these data a recent prospective study using a human model of ARDS suggests that reduced platelet activation via aspirin administration significantly reduces acute pulmonary neutrophilia ( 17 ). However, meta-analysis of clinical studies using aspirin in the management of ARDS concluded that data are insufficient to justify the use of aspirin as yet ( 44 ). Interestingly, an injurious role for platelet CLEC-2 during a mouse model of deep vein thrombosis was recently reported ( 46 ), with platelet transfusion shown to be protective in mice that were first subjected to extracorporeal circulation ( 34 ) or during mouse models of sepsis ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…3335 Despite the initial enthusiasm and encouraging results with aspirin as potential prevention or treatment for ARDS, 36 a prospective randomized trial of aspirin in at-risk patients presenting to the emergency department (The LIPS-A Randomized Clinical Trial) failed to reduce risk of ARDS compared to placebo, and the participating authors concluded that the results of their phase 2b trial did not support continuation to a larger phase 3 trial. 37 …”
Section: Discussionmentioning
confidence: 99%